Crystal structure of 7α-acetyl-6,14-endo-ethanotetrahydrothebaine, C23H29NO4 - Amani A.; Bardajee G. Rezanejade; Samavati G.; Mansouri R. (Zeitschrift für Kristallographie - New Crystal Structures, 2005)
C23H29NO4, orthorhombic, P212121 (no. 19), a = 7.352(2) Å, b = 8.856(2) Å, c = 29.340(6) Å, V = 1910.3 Å3, Z = 4, Rgt(F) = 0.048, wRref(F2) = 0.097, T = 193 K.